Penyuluhan Hukum Pencegahan Tindak Kriminal Di Kalangan Remaja - Wiwin Ariesta; Yudhia Ismail (AMMA : Jurnal Pengabdian Masyarakat, 2023)
As the only tertiary institution in Pasuruan that has a Faculty of Law within it, Universitas Merdeka Pasuruan is also responsible for making the public aware of the applicable legal rules and increasing public legal compliance. Therefore, in order to assist the government's efforts to increase public awareness and compliance with the law, especially among youth so that they can support the development and progress of the nation that has been aspired to through the progress and development of superior and noble human resources. The importance of legal awareness to every community is a must. Legal counseling which is held as a form of collaboration with the Faculty of Law, Merdeka University of Pasuruan in collaboration with the Sekarputih Village Government, Gondang Wetan District, Pasuruan Regency is expected to play an important role as one of the activities that has a positive impact in the community and is beneficial for the ongoing learning of Merdeka University Pasuruan students and the village community Sekarputih, Gondang Wetan District, Pasuruan Regency.